Multi-plane remote refocusing epifluorescence microscopy to image dynamic Ca2+ events - Lawton, P; Buckley, C; Saunter, C; Wilson, C; Corbett, A; Salter, P; McCarron, J; Girkin, J (Optical Society of America, 2019)
Rapid imaging of multiple focal planes without sample movement may be achieved through remote refocusing, where imaging is carried out in a plane conjugate to the sample plane. The technique is ideally suited to studying the endothelial and smooth muscle cell layers of blood vessels. These are intrinsically linked through rapid communication and must be separately imaged at a sufficiently high frame rate in order to understand this biologically crucial interaction. We have designed and implemented an epifluoresence-based remote refocussing imaging system that can image each layer at up to 20fps using different dyes and excitation light for each layer, without the requirement for optically sectioning microscopy. A novel triggering system is used to activate the appropriate laser and image acquisition at each plane of interest. Using this method, we are able to achieve axial plane separations down to 15  μ m, with a mean lateral stability of ≤ 0.32  μ m displacement using a 60x, 1.4NA imaging objective and a 60x, 0.7NA reimaging objective. The system allows us to image and quantify endothelial cell activity and smooth muscle cell activity at a high framerate with excellent lateral and good axial resolution without requiring complex beam scanning confocal microscopes, delivering a cost effective solution for imaging two planes rapidly. We have successfully imaged and analysed Ca2+ activity of the endothelial cell layer independently of the smooth muscle layer for several minutes.